Pengaruh Dana Pihak Ketiga dan Nilai Agunan Terhadap Pembiayaan Murabahah Bil-Wakalah Pada Bank Syariah Indonesia - Nuraini, Nuraini; Yanti, Nusantri; Naser Daulay, Aqwa (Universitas Hamzanwadi, 2024)
The aim of this research is to find out how the value of collateral and third party funds influences Murabahah Bil Wakalah financing at Bank Syariah Indonesia. To test multiple linear regression, this research uses a quantitative strategy with associative analysis and the Eviews 12 program. The financial records of PT Bank Syariah Indonesia for the period 2021–2023 are used as the population and sample in this research. The results of the analysis and testing of this research allow the following conclusions to be drawn: a. BilWakalah murabahah financing at Indonesian sharia banks benefits greatly from third party funds. b. The value of the collateral has a good and noteworthy influence on Bank Syariah Indonesia's Murabahah Bil Wakalah Financing. c. Murabahah Bil Wakalah financing at Sharia Commercial Banks in Indonesia is positively and significantly influenced by Third Party Funds and Collateral Value. This shows that Third Party Funds and the collateral value determined by Bank Indonesia have an influence on the demand for murabahah bil wakalah financing. Most Islamic banks base their murabahah margin determination on Third Party Funds. Apart from that, collateral is also a top priority in Bank Syariah Indonesia's Murabahah BilWakalah Financing program to provide confidence to the bank regarding the funds channeled in the form of financing. This is done with the hope that if a problem occurs, the guarantee or collateral can be used as a lifeline to ensure the bank's operations run smoothly